Study of Economic Performance of India due to Trade with SAARC Countries - Jain, Vranda; Kumar, Surender (Journal of Applied Business and Economics, 2018)
The paper empirically examines the trade led growth paradigm for India with respect to SAARC countries for the period 1990-2014. The paper uses the co-integration model to test the causal relationship between trade and output growth. Granger causality test is applied for the period 1994-2015 to examine the nature of relationship between variables under study. The results indicate absence of long term relationship between India’s GDP growth and trade among SAARC nations, thereby giving way to the existence of short term relationship. Granger causality revealed unidirectional nature of causality from exports to GDP and Imports to GDP for Nepal, Pakistan and Sri Lanka, GDP to export for Maldives, GDP to import for Bangladesh, Import to export for Bhutan and Sri Lanka and export to import for Pakistan.